Corrosion of steels in CO2 proceedings of the British Nuclear Energy Society international conference at Reading University, 23-24 September 1974 - Holmes, D. R. 1927-; Hill, Rodney, 1921-2011; Wyatt, L. M. (B.N.E.S., 1974)
Proceedings of an international conference held at University of Reading on 23-24 September 1974.